IMPLEMENTASI SISTEM KEAMANAN DAN HIGH AVAILABILITY PADA CLOUD SERVER MENGGUNAKAN AMAZON WEB SERVICES (AWS) - Febrian Kasmar, Andre; Wahyuna, Wahyuna; Sukma, Fanni; Amalia, Sitti (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2025)
Service availability and security are critical aspects in web server management, particularly for educational institutions utilizing cloud-based technologies. This study aims to implement a high availability and security system on the SMKN 5 Padang web server using Amazon Web Services (AWS). The methods employed include load balancing using Elastic Load Balancing to evenly distribute workloads, Auto Scaling to dynamically adjust the number of instances based on traffic load, and Wazuh as a security monitoring system to detect and respond to cyber threats such as Denial of Service (DoS) attacks. System performance was evaluated through stress testing and security log analysis. The implementation results indicate that load balancing effectively optimizes network traffic distribution, Auto Scaling maintains service availability during traffic spikes, and Wazuh successfully detects and mitigates security threats in real time. The main contribution of this research is the enhancement of cloud-based web server architecture through a high availability and adaptive security approach, which can be adopted by other educational institutions. Future research is recommended to optimize the system using artificial intelligence to improve proactive cyber threat detection and response efficiency.